PENGARUH KEAKTIFAN INTERAKSI SISWA DENGAN GURU DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR PAI SISWA SMA MUHAMMADIYAH 6 KARANGASEM PACIRAN LAMONGAN TAHUN PELAJARAN 2020/2021: PENGARUH KEAKTIFAN INTERAKSI SISWA DENGAN GURU DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR PAI SISWA SMA MUHAMMADIYAH 6 KARANGASEM PACIRAN LAMONGAN TAHUN PELAJARAN 2020/2021 - Nashrudin Abdul Khair (STAI Muhammadiyah Paciran Lamongan, 2024)
The researcher is interested in studying more deeply with the object of research all students of class XI mia 3 SMA Muhammadiyah 6 Paciran Lamongan. This researcher covers how active students are in class XI MIA 3, how are the daily test results and is there any effect of active student learning interactions on the results of PAI daily tests at SMA Muhammadiyah 6 Paciran. The research method used is a quantitative method. The research location is in SMA Muhammadiyah 6 Paciran Lamongan. with a research sample of 18 students of class XI MIA 3. data collection techniques in the form of questionnaires and documentation. Based on the results of the analysis of research data regarding the activeness of learning interactions on the learning outcomes of PAI daily test scores for students of class XI MIA 3 SMA Muhammadiyah 6 Paciran Lamongan. The results showed that there was a very significant correlation between student activity in learning and the daily test results of students at SMA MUhammadiyah 6 Krangasem. can be obtained product moment correlation with r count 0.976 > r table 0.46. it can be concluded that Ho is rejected and Ha is accepted, which means that it can be concluded that student learning activity has a positive and significant influence on the learning outcomes of PAI daily tests for class XI MIA 3 SMA Muhammadiyah 6 Paciran Lamongan.